Potential causes of male and female infertility in Qatar - Gerhild Zauner (1849408) (2020)
A steady decline in the fertility rate has been observed in Qatar during the past fifty years. Therefore, infertility is considered a national priority in Qatar, a pronatalist society. This review article summarises the potential causes of infertility that are particularly prevalent in the Qatari population. The high rate of consanguinity leading to genetic abnormalities, the high incidence of metabolic disease, environmental contamination due to the rapid urbanization and oil and natural gas extraction procedures are discussed. In addition, the particular lifestyle of the Qatari population and the influence of religion and culture on sexual and reproductive behavior in an Arab/Islamic society are considered. The active response of the state of Qatar in implementing ways to mitigate the effects of these factors to protect fertility are also presented. Other Information Published in: Journal of Reproductive Immunology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jri.2020.103173